Design and Analysis of Apple Picking Robots Based on TRIZ - Huan Yuan; Ren Gongchang; Sun Jiangong; Xu Ruoxuan (Jixie chuandong)
Aiming at the problems of low efficiency, high labor intensity and single function of picking equipment at the current stage of manual apple picking, this study is based on the TRIZ and inspired by the principle of invention, to analyze the end effector, transport device, collection box and other structures of the apple picking robot. With innovative design, a robot integrating picking, collecting and sorting functions has been designed. The D-H model of the picking manipulator is established, the working space of the robot is analyzed by Matlab, the motion simulation of the picking process of the robot is carried out by Adams, and a 1∶3 experimental prototype is made to verify the functional feasibility of each part. The results show that the functions of each part of the robot are perfect, the design is reasonable, the operation is reliable, and it meets the needs of use, which provides theoretical support for the further development and improvement of the follow-up robot.